2007
DOI: 10.1093/ps/86.7.1445
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Model of Egg Production in Broiler Breeders

Abstract: A stochastic model was developed to simulate the egg production of broiler breeders in response to changes in BW. The first step involved the construction of a diagram incorporating dependent and independent variables and their relationships to ovulation rate and egg production from 8 equations based on experimental results. The model was based on existing experimental data, and stochastic processes were invoked for 4 input parameters. Egg production curves and total egg production were simulated using inputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Such approaches, however, are either too complex, as in the case of the compartmentalization model [2], or require too many variables to determine production, as in the case of the stochastic model [3], making such models impractical under most commercial situations. Other models, such as the Gompertz nonlinear model, produce nonsensical results and are unsuitable for the kinds of variables and production data at hand, as shown in this article.…”
Section: Description Of Problemmentioning
confidence: 99%
“…Such approaches, however, are either too complex, as in the case of the compartmentalization model [2], or require too many variables to determine production, as in the case of the stochastic model [3], making such models impractical under most commercial situations. Other models, such as the Gompertz nonlinear model, produce nonsensical results and are unsuitable for the kinds of variables and production data at hand, as shown in this article.…”
Section: Description Of Problemmentioning
confidence: 99%
“…, 2012 ), predicting future records and trends ( Adams and Bell, 1980 ; Brand et al, 2012 ; Faraji-Arough et al, 2019 ; Jahan et al, 2020 ), evaluating progress through the selection process ( Savegnago et al . , 2012 ), and also estimating deviation from the expected production curve ( Alvarez and Hocking, 2007 ; Johnston and Gous, 2007 ; Faraji-Arough et al, 2018 ). Egg production curves represent stages.…”
Section: Introductionmentioning
confidence: 99%
“…The curve shape can be described by the following phases: sexual maturity, followed by increasing to maximum production, a peak production, stable decrease of egg production and persistency of production (Fialho andLedur, 1997, Grossman andKoops, 2001). It is well known that there are some aspects affect egg production including: environmental rearing conditions (i.e., temperature and humidity, Elijah and Adedapo, 2006), body weight (Álvarez andHocking, 2007 andSelvaggi et al, 2015) ,diseases either bacterial or viral (Spedding, 1988) and nutritional balance (Rozenboim et al, 2007). In poultry studies, mathematical models were found to be very useful tools to fit egg production, egg weight, growth rate, and feed intake curves (Faridi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%